Menakar Kembali Konsep Kala pada Fiʿil Māḍī Menurut Nuḥāt (Kajian Reflektif untuk Pembelajaran Bahasa Arab) - Muh Hikamudin Suyuti; Hasyim Asy'ari (Alsina : Journal of Arabic Studies, 2021)
The most often discussed topics concerning nahw (Arabic grammar) are ism (noun), fi’il (verb), and hurf (letter). Fi'il (verb) can be classified into māḍī, muḍāriʿ, and amar. As well as past (māḍī), present (muḍāriʿ), and future (mustaqbal). The study of time in Arabic is critical. The purpose of this study is to examine fiil māḍī using a content analysis method. This study reported that Arabic grammarians (Nuḥāt) have diverse opinions on time in fiʿil māḍī, particularly to state implications in the current and future time, an argument that is bolstered by the fact that the Assyrian language also uses it. In Arabic, the term fiʿil ghayr tām (Muḍāriʿ) refers to both present and future events. The researchers suggested to use several reading methods to improve students' Arabic understanding, including Al-Qirā'ah al-Muwassaʿah (Extensive Reading), Al-Fahm al-Qirā'ī (Reading Comprehension) and Al-Qirā'ah al-Nāqidah (Critical Reading).